Strategies for supporting the implementation of a task-shared psychological intervention in South Africa's chronic disease services: qualitative insights from health managers' experiences of project MIND. Issue 1 (31st December 2022) - Brooke-Sumner, Carrie; Petersen-Williams, Petal; Sorsdahl, Katherine; Kruger, James; Mahomed, Hassan; Myers, Bronwyn
ABSTRACT: Background: Although evidence indicates that task-shared psychological interventions can reduce mental health treatment gaps in resource-constrained settings, systemic barriers have limited their widespread implementation. Evidence on how to sustain and scale such approaches is scant. This study responds to this gap by examining the experiences of South African health managers involved in the implementation of a task-shared counselling service for Project MIND. Objectives: To qualitatively describe managers' experiences of implementing the MIND programme and their insights into potential strategies for supporting sustained implementation. Methods: Two focus group discussions (FGDs) and eight in-depth interviews (IDIs) were conducted with managers of urban and rural primary care facilities in the Western Cape province. All managers were female and 30–50 years old. FGDs and IDIs used an identical semi-structured topic guide to explore the experiences of the MIND programme and perceived barriers to sustained implementation. Normalisation process theory (NPT) guided the thematic analysis. Results: Four themes emerged that mapped onto the NPT constructs. First, managers noted that their relational work with staff to promote support for the intervention and reduce resistance was key to facilitating implementation. Second, managers emphasised the need for staff reorientation and upskilling to foster openness to mental health practice and for adequate time for quality counselling. Third, managers underscored the importance of strengthening linkages between the health and social service sectors to facilitate delivery of comprehensive mental health services. Finally, managers recommended ongoing monitoring of the service and communication about its impacts as strategies for supporting integration into routine practice. Conclusions: Findings contribute to the emerging literature on strategies to support implementation of task-shared interventions in low- and middle-income countries. The findings highlight the leadership role of managers in identifying and actioning these strategies. Investing in managers' capacity to support implementation of psychological interventions is critical for scale-up of these mental health innovations.